What They Don't Know Says A Lot: Residents' Knowledge of Neighborhood Crime in Contemporary China - Shen, Yinzhi (Journal of quantitative criminology, 2019)
Our study questions the common assumption of random DK responses in criminology survey data and emphasizes the importance of understanding and handling DK for gaining substantive criminological knowledge. It examines the individual-level and neighborhood-level correlates of the propensity to give the DK response to questions on individual perception of neighborhood crime in Chongqing, China.